2001
DOI: 10.1083/jcb.200103048
|View full text |Cite
|
Sign up to set email alerts
|

RhoA is required for monocyte tail retraction during transendothelial migration

Abstract: Transendothelial migration of monocytes is the process by which monocytes leave the circulatory system and extravasate through the endothelial lining of the blood vessel wall and enter the underlying tissue. Transmigration requires coordination of alterations in cell shape and adhesive properties that are mediated by cytoskeletal dynamics. We have analyzed the function of RhoA in the cytoskeletal reorganizations that occur during transmigration. By loading monocytes with C3, an inhibitor of RhoA, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
349
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(390 citation statements)
references
References 81 publications
39
349
0
2
Order By: Relevance
“…RhoA is a monomeric GTPase that is required for migration in several cell types including neutrophils (Xu et al, 2003), monocytes (Worthylake et al, 2001) and fibroblasts (Sander et al, 1999). We have demonstrated that bombesin and ET-1 activate RhoA and that the RhoA effector, ROCK, is required for bombesinstimulated migration of PC cells.…”
Section: Discussionmentioning
confidence: 89%
“…RhoA is a monomeric GTPase that is required for migration in several cell types including neutrophils (Xu et al, 2003), monocytes (Worthylake et al, 2001) and fibroblasts (Sander et al, 1999). We have demonstrated that bombesin and ET-1 activate RhoA and that the RhoA effector, ROCK, is required for bombesinstimulated migration of PC cells.…”
Section: Discussionmentioning
confidence: 89%
“…Lowering Rac1 activity resulted in an increase in RhoA activity and we found increased RhoA activity (V14RhoA) also gave rise to defective heterotypic CIL. RhoA was thought to be predominantly involved in tail retraction of migrating cells [24], however, recent studies suggest RhoA may participate in both membrane protrusion and retraction at the leading edge [20,25]. Cells expressing dominant active mDia became more invasive, possibly because mDia activates Rac1 [26].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological point of view it is important that C3 was shown to alter for example epithelial and endothelial barrier functions (Nusrat et al 1995;Stamatovic et al 2003), the signaling of immune cells including phagocytosis (Caron and Hall 1998), the production of cytokines (Chen et al 2002;Dreikhausen et al 2001), adhesion (Laudanna et al 1996), de-adhesion , and migration of immune cells (Worthylake et al 2001;Millan and Ridley 2005). A very recent study reported that C3stau-producing S. aureus form transcellular tunnels by inactivation of Rho, so-called macroapertures, which lead to the loss of barrier function in endothelial cells (Boyer et al 2006).…”
Section: The Pathogenetic Role Of C3-like Exoenzymesmentioning
confidence: 99%